Realizing single-crystalline vertically-oriented and high-density electrospun nanofibril bundles by controlled postcalcination. Issue 25 (13th June 2017) - Li, Jian-Min
Abstract : The first single-crystal, vertically-oriented and high-density ultrafine SrCO3 NFBs were achieved by controlled postcalcination of as-spun fibers. Abstract : For the first time, single-crystal (SC), vertically-oriented and high-density electrospun ultrafine nanofiber/fibre bundles (NFBs) were achieved by the controlled postcalcination of as-spun fibers. The formation of high-density SC strontium carbonate ( i.e. SrCO3 ) nanoneedles (NNs) quasi-vertically grown with an average diameter of ∼20 nm, several micrometers long that stand perpendicular to the growth surface, is demonstrated. Furthermore, under electron-beam irradiation, an individual as-calcined SC SrCO3 NN undergoes sequential structural transitions from the [110] SC—to—polycrystalline—to—[102] SC SrCO3 NN, which was revealed by in situ transmission electron microscopy. Photoluminescence quenching over the full solar spectrum range was observed in the as-calcined vertically-oriented SrCO3 NFBs.